Influences of multimedia and interactivity in augmented reality learning application in enhancing undergraduate students' motivation - Yap, Shook Chin (2024)
Augmented reality (AR) has been extensively used for education. Many studies have proved that AR provides numerous benefits in education. However, there is not much work on investigation on questions regarding how learning with AR works for students, such as how multimedia and interactivity motivates students’ learning interest. Therefore, the objectives of this study are to identify features of AR that can enhance student motivation, evaluate the effects of different combinations of multimedia elements on motivation within AR learning experiences, and assess how varying levels of interactivity in AR learning environments influence students' motivation. To explore that, an intensive literature review was conducted to identify the features that could influence learning motivation. An experiment was conducted to do two heuristic evaluations on an existing AR learning application to justify this research direction. This experiment has identified some design guidelines and acknowledged that multimedia and interactivity could be candidates for valueadded factors in AR learning applications that can enhance students’ learning motivation. To further investigate how multimedia and interactivity influence students’ learning motivation, a mobile AR learning application for students to learn basic computer knowledge, namely secondary storage devices animated augmented reality application (SDAAR) was developed. The application was made flexible to implement different multimedia elements and interactivity. The subsequent experiment investigated the influence of various combinations of multimedia elements on motivation and change or topic perception. A between-subjects design study was adopted to conduct a comparative 3 x 2 factorial design experiment with a total of 144 participants. It was found that for the lower level of Bloom’s taxonomy, 3D animation and audio description is essential to retain attention of learners. 3D animation and description to be delivered by concurrent narration with text could provide a more satisfactory learning experience. Whereas description by text only is not advisable. Experiment three investigated if a higher level of interactivity can enhance students’ learning motivation and technology acceptance. With eight different experimental conditions, a comparative study was carried out with a total of 87 participants. It was found that interactivity could significantly enhance students’ technology acceptance toward ARLE. The higher level of interactivity can enhance more confidence in users as compared to the low level of interactivity The study contributes to the field by providing a comprehensive understanding of how specific features of AR can enhance student motivation. It reveals the effects of various multimedia combinations and levels of interactivity within AR learning environments, offering insights into how these factors individually and interactively impact motivation. This knowledge can guide the design and implementation of more effective AR educational tools, tailored to maximize student engagement and learning outcomes.